(untitled) (Marketing Jurnali, 2026)
This study examined the evolution of Uzbekistan’s investment climate since 2017 and its relationship with economic growth. Drawing on national legislation, official statistics and the reporting of international organisations, the study assessed the effects of currency liberalisation, tax and customs reform, privatisation, investor protection and the reduction of administrative barriers on investment activity. The preferences available to investors, including special economic zones, tax and customs exemptions and individually negotiated investment agreements, were systematised, and the outcomes of the Tashkent International Investment Forum were evaluated by distinguishing announced agreements from utilised resources and balance-of-payments inflows. The findings showed that the improvement of the investment climate coincided with a sustained expansion of fixed capital formation and an acceleration of output growth, while the two reporting systems used for foreign investment diverge substantially. The study proposed practical recommendations for raising the quality, transparency and developmental impact of investment policy.